Research into the correlation between positional skull deformation and motor performance of infants aged under 4 months - Tianqi Huang; Wenzao Li; Chengju Wang; Fuxiang Qu; Qiuxia Yang; Qiuming Pan; Xiaoqin Pu; Can Xiao; Yi Cai; Meifeng Xia; Yuping Zhang (BMC, 2023)
Abstract Objective To investigate the correlation between positional skull deformation (PD) and motor performance of infants under 4 months of age. Methods Infants aged under 4 months were enrolled in the children's healthcare and the premature infants follow-up Clinic of the Second Affiliated Hospital of Army Military Medical University. The cranial vault asymmetry (CVA) and cephalic index (CI) were calculated in all infants, and the infant motor performance test (TIMP) was used to evaluate the infant motor performance. The motor performances of infants with different types and degrees of PD were compared, so were the incidences of PD in infants with different motor performance levels. Results Overall, 2118 infants were recruited and divided according to the types of PD and TIMP scores. The comparison of TIMP scores within different types of PD at different months of age showed that, regardless of the types of PD, TIMP scores of infants with PD were lower than those of normal infants. In particular, the difference in TIMP scores was statistically significant (P < 0.05) in infants with dolichocephaly, plagiocephaly,dolicho-plagiocephaly and brachy-plagiocephy. In addition, the comparison of CVA values of infants with different TIMP score levels at different months of age showed that the CVA values of the extremely low-level group were significantly higher than those of the medium-level and high-level group, especially in the 3-month-old and 4-month-old groups, which showed significant statistical differences (P < 0.05). Conclusions PD and motor performance of infants aged under 4 months seem to interact and influenc each other. The more serious the severity of PD were,the worse the motor performance of infants. Conversely, the incidence of PD increased in infants with poor motor performance.